Canadian Working-Class Environmentalism, 1965–1985 - MacPhee, Katrin (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2014)
The historiographies of Canadian labour and environmental activism have largely overlooked the existence of a distinctly working-class environmental consciousness in Canada between 1965 and 1985. This worker-oriented environmentalism was expressed in three separate but interrelated strategies. First, labour activists in the 1960s through to the 1980s undertook independent research into the environmental contaminants present in their own workplaces and subsequently released into the larger environment. Second, a number of Canadian unions consistently endeavoured to compel branches of the Canadian government to adopt and enforce strict environmental policies and regulations. Third, Canadian union members exercised the weapons at their disposal – collective bargaining, demonstrations, and strikes – to prevent harm to environmental and human health alike. Through an analysis of these realms of struggle, I outline an environmentalism born of a class analysis of health and disease under capitalism.